2010
DOI: 10.3109/13682820903461493
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers with autism show greater impairment in receptive compared with expressive language abilities

Abstract: Recognition of the marked receptive language impairment relative to expressive language, found to affect at least one-third of preschoolers with autism in this sample, has important implications for interacting with these children and for informing appropriate targets in language and communication intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
180
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(213 citation statements)
references
References 33 publications
28
180
4
1
Order By: Relevance
“…Approximately half of the group achieved equal levels for receptive as for expressive language, but a substantial part showed a considerably lower level for comprehension than for production. All findings about language profiles are in line with the results for toddlers with ASD (e.g., Hudry et al 2010;Weismer et al 2010). However, studies in older high functioning children with ASD found no differences between expressive and receptive language abilities (Jarrold et al 1997;Kjelgaard and Tager-Flusberg 2001).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Approximately half of the group achieved equal levels for receptive as for expressive language, but a substantial part showed a considerably lower level for comprehension than for production. All findings about language profiles are in line with the results for toddlers with ASD (e.g., Hudry et al 2010;Weismer et al 2010). However, studies in older high functioning children with ASD found no differences between expressive and receptive language abilities (Jarrold et al 1997;Kjelgaard and Tager-Flusberg 2001).…”
Section: Discussionsupporting
confidence: 79%
“…Many low-functioning children with ASD have receptive skills that are more impaired than their expressive language skills. Particularly in the case of more verbal children, communication partners will be misled by the level of expressive language abilities, assuming a comparable level of comprehensions skills (Hudry et al 2010;Noens and Van Berckelaer-Onnes 2004). In typical development, comprehension always precedes language production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We would be unwise to speculate too far on the basis of one child's profile, but we notice that Child 3 does not show the pattern of worse performance on the form recall task compared to the two recognition tasks that was reported by Anonymous (in press) and which is also seen among our participants in Table 3; this unusual profile is consistent with reports of autism in spoken languages, where the delay in receptive vocabulary is greater than the delay in expressive vocabulary (Charman, Drew, Baird, & Baird, 2003;Hudry et al, 2010). Studies which assess vocabulary development in deaf children with a wide range of additional disabilities might contribute important information about (the) possible effects of disabilities on word learning that are most common within the group of deaf language users.…”
Section: Discussionsupporting
confidence: 76%
“…Siguiendo un patrón inverso al del desarrollo típico, es decir, suelen tener mayores dificultades en comprensión que en producción (Hudry et al 2010;Weismer, Lord y Esler, 2010). En los casos en los que se observa un nivel elevado de lenguaje expresivo suele ser debido a ecolalias o a la reproducción de lenguaje memorizado (Maljaars, Noens, Scholte y van Berckelaer-Onnes, 2012).…”
Section: Introductionunclassified